Using human resource data to track innovation summary of a workshop - Merrill, Stephen A.; McGreary, Michael; ProQuest (Firm) (Washington, D.C. : National Academy Press, 2002)
"This volume is the summary of a second STEP workshop, chaired by board memder Mark Myers, formerly chief technical officer of Xerox Corporation. The workshop explored how data on scientists, engineers, and other professionals-data on their training and skills, mobility and career paths, use of time, relationships across institutions and sectors, and productivity-can be used to illuminate aspects of innovation that current R&D, patent and other data, by themselves, do not fully capture." -- p. viii, Preface.
I. What role for human resource data in tracking innovation? -- II. Principal sources of human resource data -- III. Research applications of human resource data -- IV. Enhancing the utility of human resource data.
Includes bibliographical references.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Technological innovations -- United States -- Congresses; Industrial policy -- United States -- Congresses; Research, Industrial -- United States -- Congresses; Technology and state -- United States -- Congresses; Science and state -- United States -- Congresses; Electronic books